Increase in insurance losses caused by North Atlantic hurricanes in a warmer climate - Francesco Comola; Bernhard Märtl; Hilary Paul; Christian Bruns; Klaus Sapelza (Communications Earth & Environment)
Abstract North Atlantic hurricanes are a major driver of property losses in the United States and a critical peril for the reinsurance industry globally. We leverage insurance loss data and stochastic modeling to investigate the impacts of projected changes in hurricane climatology on the insurance industry, for  +2 °C and  +4 °C warming scenarios. We find that, relative to the historical baseline 1950-2022, expected changes in wind speed and rainfall may increase hurricane losses by 5% −15% (+2 °C) and 10% − 30% (+4 °C), with greater impacts at lower return periods than in the tail. The historical 100-year loss event may therefore be exceeded on average every 80 years (+2 °C) and 70 years (+4 °C). The expected changes in average annual loss are projected to be 10% (+2 °C) and 15% (+4 °C), with the largest relative increase attributable to precipitation-induced losses. Under the extreme SSP5-8.5 scenario, the expected loss inflation due to climate change is thus on the order of 0.5% per annum.